Acid-triggered two-stage superlarge redshift absorption for turn-on type photothermal conversion at the first and second near-infrared window. Issue 5 (18th January 2023) - Xu, Xiao-Qi; Ma, Yingchao; Zhao, Ning-jiu; Tian, Shangjie; Lei, Hechang; Wang, Yapei
Abstract : A series of "turn-on" type NIR materials are developed with two-stage superlarge redshifted absorption in the first and second NIR window under the stimulation of protonation for smart photothermal conversion. Abstract : Benefiting from a deep tissue penetration and high allowed maximum exposure power, near-infrared (NIR)-II (1000–1350 nm) absorbers for photothermal conversion have received considerable attention in a myriad of fields. To promote specificity, introducing a stimuli-responsive behaviour provides a promising approach for achieving intelligent NIR-II photothermal conversion under varied environments. However, NIR-II absorbers are currently mostly constructed by conjugated polymers, which can hardly be modified with stimuli-responsive segments, while small molecular chromophores can be simply functionalized, yet their absorption bands are extremely limited by their short conjugation length. To address this inherent contradiction, a series of "turn-on" types of absorbers were developed with a two-stage superlarge redshifted absorption in the first and second NIR window under the stimulation of protonation. The mechanism of such bathochromic shift behaviours was further studied through EPR spectroscopy and DFT calculations. Under the irradiation of 808 nm and 1064 nm lasers, the photothermal conversion abilities could be switched on and off synchronously. We believe "turn-on" types of NIR-II absorbers will offer great inspiration for designing smart materials with controllable NIR-I and NIR-II photothermal conversion capabilities.